Platelet markers correlate with glycemic indices in diabetic, but not diabetic-myelodysplastic patients with normal platelet count. - Dalamaga, Maria; Karmaniolas, Konstantinos; Lekka, Antigoni; Antonakos, George; Thrasyvoulides, Apollon; Papadavid, Evangelia; Spanos, Nikolaos; Dionyssiou-Asteriou, Amalia (Dis Markers, 2010)
BACKGROUND: Altered thrombocyte morphology and function have been reported in patients with diabetes mellitus (DM) type 2. The aim of the present study was to determine the associations between platelet morphology markers and hemoglobin A1C (HbA(1c)), fasting glucose (FG), hypertension and coronary heart disease (CHD) in patients with myelodysplastic syndromes (MDS) and DM, in patients with DM and in controls. METHODS: This cross-sectional study included 30 cases with primary MDS with normal platelet count and non-insulin dependent diabetes, 30 non-insulin dependent diabetic patients and 30 non-diabetic, non-MDS controls matched on age and gender. RESULTS: After adjusting for body mass index, platelet number, CHD and hypertension, HbA(1c) and FG were significant predictors of mean platelet volume (MPV) and platelet distribution width (PDW) in diabetic patients. There was no correlation between platelet parameters and HbA(1c) or FG in diabetic MDS patients. In controls, FG and hypertension predicted significant differences in platelet morphology. Platelet count correlated with platelet morphology in diabetic MDS and control groups, but not in diabetics. CONCLUSIONS: MPV and PDW are associated with glycemic indices in diabetic patients but not in diabetic MDS patients with normal platelet counts. Non-diabetic controls also exhibit FG related changes in platelet morphology. This suggests other factors inherent to bone marrow dysplasia, platelet turnover and biochemistry, or vascular environment affect platelet morphology in diabetic MDS patients even with normal platelet count. Platelet morphology in this population may be an early marker for myelodysplasia. These findings also support platelet morphology change as a marker for elevated macrovascular disease risk.
Keywords: Aged; Biomarkers; Blood Glucose; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Female; Humans; Male; Myelodysplastic Syndromes; Platelet Count